Genetic and other factors determining mannose-binding lectin levels in American Indians: the Strong Heart Study - Zhang Ying; MacCluer Jean W; North Kari E; DeCroo Susan; Ferrell Robert E; Best Lyle G; Lee Elisa T; Howard Barbara V; Umans Jason; Palmieri Vittorio; Garred Peter (BMC, 2009)
Abstract Background Mannose-binding lectin (MBL) forms an integral part of the innate immune system. Persistent, subclinical infections and chronic inflammatory states are hypothesized to contribute to the pathogenesis of atherosclerosis. MBL gene (MBL2) variants with between 12 to 25% allele frequency in Caucasian and other populations, result in markedly reduced expression of functional protein. Prospective epidemiologic studies, including a nested, case-control study from the present population, have demonstrated the ability of MBL2 genotypes to predict complications of atherosclerosis,. The genetic control of MBL2 expression is complex and genetic background effects in specific populations are largely unknown. Methods The Strong Heart Study is a longitudinal, cohort study of cardiovascular disease among American Indians. A subset of individuals genotyped for the above mentioned case-control study were selected for analysis of circulating MBL levels by double sandwich ELISA method. Mean MBL levels were compared between genotypic groups and multivariate regression was used to determine other independent factors influencing MBL2 expression. Results Our results confirm the effects of variant structural (B, C, and D) and promoter (H and Y) alleles that have been seen in other populations. In addition, MBL levels were found to be positively associated with male gender and hemoglobin A1c levels, but inversely related to triglyceride levels. Correlation was not found between MBL and other markers of inflammation. Conclusion New data is presented concerning the effects of known genetic variants on MBL levels in an American Indian population, as well as the relationship of MBL2 expression to clinical and environmental factors, including inflammatory markers.